Enhancing public health through ocean research—a model for global partnership - Piccioli, Andrea; Lucentini, Luca; Muratore, Anna; Risoluti, Roberta; Briancesco, Rossella; La Rosa, Giuseppina; Notargiacomo, Lorenza; Mattei, Giorgia; Mattei, Daniela; Di Gregorio, Federica Nigro; Veschetti, Enrico; Bogialli, Sara; et al. (Frontiers in Climate, 2025)
Understanding the connection between ocean health and human health is currently limited and fragmented, calling for transdisciplinary research and strategic action. The contribution of public health experts alongside marine scientists are essential for a comprehensive understanding of the health-environment-climate nexus in a Planetary Health perspective. This paper proposes a novel Model for a standing Global Partnership, the SeA Care project. This initiative aims to align efforts within the framework of the Sustainable Development Goals merging the principles of Planetary Health with the “One Water” approach. By doing so it seek to foster the development and assessment of new strategies for oceanwide surveillance focusing on adaptation, mitigation and prevention.